Test-Retest Reliability of Velocity and Power in the Deadlift and Squat Exercises Assessed by the GymAware PowerTool System - Grgic, Jozo; Scapec, Bela; Pedisic, Zeljko; Mikulic, Pavle (Frontiers in Physiology, 2020)
We explored the test-retest reliability of velocity and power assessed by the GymAware PowerTool system (GYM) in the deadlift and squat by simulating a context with and without a familiarization session. Sixteen resistance-trained individuals completed three testing sessions. In all sessions, velocity and power were assessed by the GYM system in the deadlift and squat exercises with loads of 30%, 45%, 60%, 75%, and 90% of one-repetition maximum. The consistency of test results between the first session and the second session was considered to represent the reliability with no familiarization session. The consistency of test results between the second session and the third session was considered to represent the reliability with one familiarization session because the first session simulates a familiarization session. Intraclass correlation coefficients (ICCs) ranged 0.63–0.99 in the deadlift, and 0.78–0.99 in the squat. ICCs were higher than 0.75 for 93% and 100% of all deadlift and squat tests, respectively. For velocity and power, standard error of measurement ranged 0.03–0.08 m/s and 20–176 W, respectively. The coefficient of variation ranged 2.2%–10.6% for the deadlift and 2.6%–6.9% for the squat tests. Except for peak and mean velocity at 30% of 1RM in the squat, we found no significant improvements in reliability with a familiarization session. The test-retest reliability of velocity and power assessed by the GYM system was moderate-to-excellent for the deadlift and good-to-excellent for the squat. Reliability of velocity and power did not seem to improve with a familiarization session.